IMPLEMENTASI MEDIA EDUKATIF FLASHCARD UNTUK MENINGKATKAN KEMAMPUAN MEMBACA MATERI BAHASA INDONESIA KELAS 1 SD - Annisaus Sholikhah; Ina Agustin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to implement educational flashcard media to improve early reading skills in first-grade elementary school students, specifically in the subject of Indonesian Language with the theme “Personal Hygiene and Health.” The background of this research is based on the low reading motivation and initial reading abilities of early-grade students, along with the limited and conventional learning media used by teachers. The research method employed is Research and Development (R&D), using the ADDIE development model which includes five stages: Analyze, Design, Develop, Implement, and Evaluate. The research subjects consisted of 26 first-grade students from UPT Private Elementary School in Regency X. Data were collected using observation sheets, interviews, questionnaires, and reading tests. The results showed that the developed flashcard media was highly valid based on expert evaluations in content, media design, and language. It was also considered practical according to the responses from teachers and students. The effectiveness was demonstrated through significant improvement in students' reading scores, with more than 75% achieving scores above the Minimum Mastery Criteria (KKM). In conclusion, educational flashcard media is proven to be an effective, engaging, and interactive tool to support reading instruction in early grade levels, especially for improving word recognition, syllable decoding, and reading comprehension.